2017
DOI: 10.1249/mss.0000000000001300
|View full text |Cite
|
Sign up to set email alerts
|

Practicing the Test Produces Strength Equivalent to Higher Volume Training

Abstract: These findings suggest that neither exercise volume nor the change in muscle size from training contributed to greater strength gains compared with just practicing the test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 25 publications
6
85
2
2
Order By: Relevance
“…In this study, the mean difference between the two conditions in the total number of repetitions was 3 (95% CI: 0.1 to 5.2). Such an increase in muscular endurance following acute caffeine ingestion is similar to improvements noted following eight weeks of regimented resistance training (Mattocks et al, 2017), highlighting the possible magnitude of caffeine's effects.…”
Section: Does Decaffeinated Coffee Block Caffeine's Ergogenic Effects?supporting
confidence: 53%
“…In this study, the mean difference between the two conditions in the total number of repetitions was 3 (95% CI: 0.1 to 5.2). Such an increase in muscular endurance following acute caffeine ingestion is similar to improvements noted following eight weeks of regimented resistance training (Mattocks et al, 2017), highlighting the possible magnitude of caffeine's effects.…”
Section: Does Decaffeinated Coffee Block Caffeine's Ergogenic Effects?supporting
confidence: 53%
“…Because the patients were women, sedentary (with ~60% sedentary time per day), postmenopausal, fairly functional, and in remission or with mild‐to‐moderate disease activity, these data cannot be extrapolated to patients with different characteristics (e.g., those with a more severe disease). Because we opted for 1RM reassessments throughout the training protocol, one might consider those as supplemental high‐load training sessions, possibly affecting strength gains . However, in the current study, in addition to the control group, the other 2 groups also had multiple familiarization sessions before beginning the trial, and only 2 reassessments were conducted during training (at weeks 4 and 8), which is far less than previously shown to affect strength, thus mitigating a possible confounding effect and strengthening the current design.…”
Section: Discussionmentioning
confidence: 91%
“…Muscle hypertrophy remains a candidate for strength adaptation; however, in many situations it has been suggested that hypertrophy plays a negligible role. 6,7 Increases in strength following a resistance training program are often measured using several assessments, some of which may be considered specific to the training stimulus, whilst others appeal less to specificity (i.e., involving the same muscle groups but different contraction type/movement). It has been suggested that multiple strength measures may better reflect strength adaptations acquired from a resistance training program.…”
mentioning
confidence: 99%